The Debate over the Origin of the Great Recession in the United States - Mario Rojas Miranda (Norteamérica)
This article analyzes the debate over the origins of the Great Recession in the United States. The author analyzes three perspectives: the first is the position spearheaded by John B. Taylor, who proposes the Great Deviation. The second is that of Alan Greenspan, Donald L. Khon, Ben S. Bernanke, Frederic S. Mishkin, and Lars E. O. Svensson, who attribute the crisis to a global imbalance between savings and investment. The third is the point of view of Robert Hetzel, Anna Schwartz, and Alan Meltzer, well-known inheritors of the monetarist tradition, who all accuse the authorities of having provoked the crisis and implemented the wrong responses. In conclusion, the author presents the opinion of two Nobel Prize winners in economics, Paul Krugman and Joseph Stiglitz.